Pengolahan Citra Untuk Mengetahui Tingkat Perubahan Noise Pada Media Penampung Air Menggunakan Metode Histogram Citra - Dewi, Guswita (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
An image is rich in information, but often the images we possess undergo image quality degradation, such as a decrease in image quality due to defects or noise, overly contrasting colors, lack of sharpness, blurring, and so on. Image enhancement is a commonly used method to improve image quality. Image enhancement aims to achieve a visually better representation of the image. Various techniques or methods are employed in image enhancement, including the use of histogram equalization methods. The use of digital images is increasing due to the advantages they offer, such as ease of obtaining, reproducing, and processing images. However, not all digital images have a visually pleasing appearance. Dissatisfaction may arise due to noise, poor lighting quality in digital images being too dark or too bright. Therefore, methods are needed to improve the quality of these digital images. To enhance the image quality in terms of color contrast, treatment can be applied to its histogram. The treatment referred to in this article is histogram equalization on grayscale images. An image histogram is considered good if it can involve all possible levels or shades in grayscale. Of course, the goal is to display details in the image for easy observation. The process of changing and improving digital image quality is carried out using MATLAB.